A importância dos círculos de cultura na educação em direitos humanos da juventude proletária: a experiência do Parque Genibaú - Costa, Francisco Daniel Araujo da (2023)
This dissertation aimed to identify and discuss the impacts of the experience of a group of young people from the neighborhood of Parque Genibaú in the city of Fortaleza (Ceará), who proposed to organize a Culture Circle, as an experience and initiative of a social movement to develop actions in the local community. Hereupon, we sought to address the following question: Considering the experience of the Culture Circle and Proletarian Organization - CCOP of Parque Genibaú, in the city of Fortaleza, what are the signs of youth protagonism, social pedagogy and Freirean thought and its contribution to the socio-educational process formation of Proletarian and Peripheral Youth? To work on this research question, we approached the theoretical contribution and the discussions around Education in Human Rights in the context of a scenario of crisis of rights, and also, the concepts of Culture Circle, of Knowledge Production and Awareness, from the thought of Paulo Freire. As a methodological route, a reading lens of the real used by the Christian Worker Youth movement, developed by Joseph Leo Cardijn, was used: the See, Judge, Act. A bibliographic research was also carried out, with a survey of Freire's texts concerning the theme, such as Conscientização; Educação Como Prática de Liberdade; and Pedagogia do Oprimido. In the documentary analysis, we took the texts produced by the members of CCOP (Culture Circle and Proletarian Organization) in the period of performance. In the field research, CCOP participants were invited to participate in semi structured interviews, which were analyzed using a qualitative approach, in accordance with HAGUETE(2001) and MINAYO(2009) conception. And finally, we used the Dialogic Discourse Analysis - DDA, as conceived by Bakhtin, that is, where the concepts of enunciation, subject, dialogism, speech and speech genres have a preponderant role in the development of the research. It was concluded that Culture Circles constitute a fundamental instrument for a Popular Education project and in the promotion of Education in and for Human Rights. In particular, we found that those who experienced the CCOP at Parque Genibaú bring with them a strong influence of everything that was built there, especially in their professional achievements, engagement in social struggles and promotion of Human Rights.